If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -4y + 6) * dx = (3 + -1x + -1y) * dy Reorder the terms: (6 + 2x + -4y) * dx = (3 + -1x + -1y) * dy Reorder the terms for easier multiplication: dx(6 + 2x + -4y) = (3 + -1x + -1y) * dy (6 * dx + 2x * dx + -4y * dx) = (3 + -1x + -1y) * dy Reorder the terms: (6dx + -4dxy + 2dx2) = (3 + -1x + -1y) * dy (6dx + -4dxy + 2dx2) = (3 + -1x + -1y) * dy Reorder the terms for easier multiplication: 6dx + -4dxy + 2dx2 = dy(3 + -1x + -1y) 6dx + -4dxy + 2dx2 = (3 * dy + -1x * dy + -1y * dy) Reorder the terms: 6dx + -4dxy + 2dx2 = (-1dxy + 3dy + -1dy2) 6dx + -4dxy + 2dx2 = (-1dxy + 3dy + -1dy2) Solving 6dx + -4dxy + 2dx2 = -1dxy + 3dy + -1dy2 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add 'dxy' to each side of the equation. 6dx + -4dxy + dxy + 2dx2 = -1dxy + 3dy + dxy + -1dy2 Combine like terms: -4dxy + dxy = -3dxy 6dx + -3dxy + 2dx2 = -1dxy + 3dy + dxy + -1dy2 Reorder the terms: 6dx + -3dxy + 2dx2 = -1dxy + dxy + 3dy + -1dy2 Combine like terms: -1dxy + dxy = 0 6dx + -3dxy + 2dx2 = 0 + 3dy + -1dy2 6dx + -3dxy + 2dx2 = 3dy + -1dy2 Add '-3dy' to each side of the equation. 6dx + -3dxy + 2dx2 + -3dy = 3dy + -3dy + -1dy2 Combine like terms: 3dy + -3dy = 0 6dx + -3dxy + 2dx2 + -3dy = 0 + -1dy2 6dx + -3dxy + 2dx2 + -3dy = -1dy2 Add 'dy2' to each side of the equation. 6dx + -3dxy + 2dx2 + -3dy + dy2 = -1dy2 + dy2 Combine like terms: -1dy2 + dy2 = 0 6dx + -3dxy + 2dx2 + -3dy + dy2 = 0 Factor out the Greatest Common Factor (GCF), 'd'. d(6x + -3xy + 2x2 + -3y + y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(6x + -3xy + 2x2 + -3y + y2)' equal to zero and attempt to solve: Simplifying 6x + -3xy + 2x2 + -3y + y2 = 0 Solving 6x + -3xy + 2x2 + -3y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-6x' to each side of the equation. 6x + -3xy + 2x2 + -3y + -6x + y2 = 0 + -6x Reorder the terms: 6x + -6x + -3xy + 2x2 + -3y + y2 = 0 + -6x Combine like terms: 6x + -6x = 0 0 + -3xy + 2x2 + -3y + y2 = 0 + -6x -3xy + 2x2 + -3y + y2 = 0 + -6x Remove the zero: -3xy + 2x2 + -3y + y2 = -6x Add '3xy' to each side of the equation. -3xy + 2x2 + -3y + 3xy + y2 = -6x + 3xy Reorder the terms: -3xy + 3xy + 2x2 + -3y + y2 = -6x + 3xy Combine like terms: -3xy + 3xy = 0 0 + 2x2 + -3y + y2 = -6x + 3xy 2x2 + -3y + y2 = -6x + 3xy Add '-2x2' to each side of the equation. 2x2 + -3y + -2x2 + y2 = -6x + 3xy + -2x2 Reorder the terms: 2x2 + -2x2 + -3y + y2 = -6x + 3xy + -2x2 Combine like terms: 2x2 + -2x2 = 0 0 + -3y + y2 = -6x + 3xy + -2x2 -3y + y2 = -6x + 3xy + -2x2 Add '3y' to each side of the equation. -3y + 3y + y2 = -6x + 3xy + -2x2 + 3y Combine like terms: -3y + 3y = 0 0 + y2 = -6x + 3xy + -2x2 + 3y y2 = -6x + 3xy + -2x2 + 3y Add '-1y2' to each side of the equation. y2 + -1y2 = -6x + 3xy + -2x2 + 3y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = -6x + 3xy + -2x2 + 3y + -1y2 Simplifying 0 = -6x + 3xy + -2x2 + 3y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| 3tan^2x+4=5 | | (6)(3i+4)(1)+(4y+1)(2i)=(8iy+2i)+(18i+24) | | 19x+13y=7 | | -8x+4y=-12 | | 15-d=8 | | 0.045x-5/8y=120 | | x^8-26x+25=0 | | 2x+14i=1 | | (x^3+3x^2-16x-48)=0 | | -37+46.98-(-0.02)= | | 5s-(100+2s)=0 | | 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 | | 5849=3.14x*81 | | 11w=132 | | -30=x+12 | | 17.8-(-4.006)-22= | | 4(-7e+9)+6=82 | | 46=(-6t)-8 | | (16x^5-x)(4x^2-9)=0 | | 4+(19-42)2= |